Numerical characterizations for compressive behaviors of warp-knitted spacer fabrics with multi-layers from simplified finite element model. (30th June 2022) - Yu, Shuang; Liu, Haisang; Wu, Shuangquan; Ma, Pibo
Warp-knitted spacer fabrics (WKSFs) with multi-layers, one of the extraordinary promising materials, are of great significance for structural uses in aerospace, military, construction, building, transportation, and so on. Compressive property is one of the important properties of WKSFs with multi-layer. In order to better understand the flat plate compressive mechanism of WKSFs with multi-layers, simplified models of WKSFs with multi-layers were constructed and their flat plate compression behaviors were simulated by finite element method. The relationship between the number of layers and compressive performance of WKSFs with multi-layers was studied by combining experiment and finite element simulation. The results showed the spacer monofilaments bear the main stress during the compression process. And the larger stress appears at the inflection point of the spacer monofilaments where the bending is serious and contact points among WKSFs with multi-layers. The compressive stiffness increases with the increase of layers in the later stage of compression. The developed finite element models have successfully simulated the flat plate compression stress-strain relationships of WKSFs with multi-layers, which are basically consistent with the general trend of test results, revealing the compression deformation mechanism and providing theoretical reference for the practical application of WKSFs with multi-layers.